Transcriptome analysis of Ganoderma lingzhi (Agaricomycetes) response to Trichoderma hengshanicum infection - Wang, Tiantian; Li, Xiaobin; Zhang, Chunlan; Xu, Jize (Frontiers in Microbiology, 2023)
Green mold caused by Trichoderma spp. has become one of the serious diseases threatening the production of Ganoderma lingzhi. To understand the possible resistance mechanism of G. lingzhi response to Trichoderma hengshanicum infection, we examined the G. lingzhi transcript accumulation at 0 h, 12 h, and 24 h after T. hengshanicum inoculation. The gene expression analysis was conducted of the interaction between G. lingzhi and T. hengshanicum using RNA-Seq and digital gene expression (DGE) profiling methods. Transcriptome sequencing indicated that there were 162 DEGs at three infection time points containing 15 up-regulated DEGs and 147 down-regulated DEGs. Resistance-related genes thaumatin-like proteins (PR-5s) gene, phenylalanine ammonia-lyase gene, and Beta-1,3-glucan binding protein were significantly up-regulated. At the three time points of infection, the HSPs genes of G. lingzhi were down-regulated. The down-regulation of HSPs genes led to the inhibition of heat shock protein function, which may be compromised the heat shock protein-mediated defense signaling transduction pathway, leading to G. lingzhi susceptibility. Pathway enrichment analyses showed that the main enriched pathways by G. lingzhi after infection were Sphingolipid metabolism, Ether lipid metabolism, and Valine, leucine and isoleucine degradation pathway. Overall, the results described here improve fundamental knowledge of molecular responses to G. lingzhi defense and contribute to the design of strategies against Trichoderma spp..